Yatırım fonlarının Türk hukuku açısından değerlendirilmesi - Akyıldız, Bengü (My University, 2003)
Türk hukukunda yatırım fonları, 1987 yılında kurulmaya başlanmış ve o zamandan beri gelişen bir süreç içine girmiştir. Yatırım fonları Türkiye'de riskin dağıtılması ve inançlı mülkiyet esaslarına göre faaliyet gösteren, yatırımcıların katılma belgesi karşılığı katıldıkları sermaye piyasası kurumudur. Yatırım fonları, sermaye piyasasının gelişmesi için çok önemlidir. Ayrıca Yatırım fonları yatırımcılara güvenli ve istikrarlı getiri sağlama aracıdır. Bu yüzden yatırım fonlarının çeşitleri arttırılmalı ve yaygınlığı sağlanmalıdır. The first mutual funds are established in Turkey in 1987 and ever since are in a developing process. In Turkey mutual funds are one of the capital market institutions which manage portfolios on the basis of principle of risk distribution and fiduciary ownership on the account of investors who are attended to funds with participation certificates. Mutuals funds are so important for the development of the capital market. In addition, mutual funds are the instruments to get the investors safe and stable income. So, the kinds of mutual funds should be increased and it should be provided them to be more common.
Keywords: Hukuk; Özel Hukuk; Yatırım Fonları